Impact of bio-alcohol fuels combustion on particulate matter morphology from efficient gasoline direct injection engines. (15th November 2018) - Hergueta, C.; Tsolakis, A.; Herreros, J.M.; Bogarra, M.; Price, E.; Simmance, K.; York, A.P.E.; Thompsett, D.
Graphical abstract: Highlights: Bio-alcohol fuel properties on GDI engines affects morphological characteristics of particles. E25 & B33 fuel blends emitted smaller primary particles than gasoline combustion. B33 combustion significantly reduced particle emissions with respect to gasoline. B33 & gasoline formed larger agglomerates than E25 combustion. E25 emitted more like-chain particles than B33 and gasoline engine operation. Abstract: The requirements for controlling particulate emissions in gasoline direct injection (GDI) engines, particularly in hybrid vehicles (where frequent cold-start event impact on both, particles characteristics and catalytic aftertreament efficiency), nesesitates the need for understanding their formation mechanism and their morphological characteristics. The findings described in this investigation have significance in the design of efficient Gasoline Particulate Filters (GPFs) and the development of computational models that predict particle filtration and oxidation processes. Morphological analysis of the particulate emissions from the combustion of commercial gasoline and two bio-alcohol blends: of 25% v/v ethanol in gasoline and 33% v/v butanol and 67% v/v gasoline, in a modern GDI engine has been carried out using a transmission electron microscopy. The primary particle size distribution from the combustion of butanol-gasoline blend was slightly smaller compared to gasoline, while the mean primary particle diameter was 3 nm smaller from the combustion of ethanol-gasoline fuel. This decrease in primary particle size for ethanol-gasoline blend was also reflected in a reduction of the mean radius of gyration and mean number of primary particles per agglomerate. The combustion of butanol-gasoline blend induced improved particle oxidation rates during the combustion process and post-oxidation stage, and led in 80% and 60% reduction in particle concentration in the engine exhaust when compared to the combustion of gasoline and ethanol-gasoline blend, respectively. Additionally, the estimation of the particle fractal dimension through the use of fractal equation, minimum bonding rectangle method and root form factor showed comparable results for butanol-gasoline and gasoline, with the particle agglomerates being more compact than the ethanol-gasoline fuel, where more chain like particles are seen. Therefore, particles emitted from the combustion of ethanol-gasoline fuel are easier to be trapped (lower fractal dimension) and present a higher reactivity (high surface/volume ratio) compared to particles emitted from gasoline combustion.